2021
DOI: 10.3390/molecules26051388
|View full text |Cite
|
Sign up to set email alerts
|

Microorganisms as a Potential Source of Molecules to Control Trypanosomatid Diseases

Abstract: Trypanosomatids are the causative agents of leishmaniasis and trypanosomiasis, which affect about 20 million people in the world’s poorest countries, leading to 95,000 deaths per year. They are often associated with malnutrition, weak immune systems, low quality housing, and population migration. They are generally recognized as neglected tropical diseases. New drugs against these parasitic protozoa are urgently needed to counteract drug resistance, toxicity, and the high cost of commercially available drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…The most common approaches to obtain new biosynthetic agents are based on searches in isolated habitats, and that impose conditions for this microbe to evolve genetically and possess unique chemical structures with possible bioactivity (Fig. 2) [28][29][30].…”
Section: Developmentmentioning
confidence: 99%
“…The most common approaches to obtain new biosynthetic agents are based on searches in isolated habitats, and that impose conditions for this microbe to evolve genetically and possess unique chemical structures with possible bioactivity (Fig. 2) [28][29][30].…”
Section: Developmentmentioning
confidence: 99%
“…Microorganisms might be a potential source of molecules to control parasitic infections such as Chagas disease [ 8 ], which is a trypanosomiasis that is considered neglected by the World Health Organization (WHO). This condition affects over six million people worldwide, mainly in Latin America [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, several reviews have reported the bioactivity of natural products against protozoan neglected diseases [ 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. However, natural products described in these reviews were obtained from different sources, including microbial [ 19 ], endophytes [ 20 ] and other fungi [ 21 ], marine [ 22 ], or animal origins [ 23 , 24 ]. Some reviews also present a mix of natural compounds origins [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%